1997
DOI: 10.1097/00007632-199711150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Conservatively Managed Rheumatoid Arthritis Patients With Myelopathy

Abstract: The clinical results for rheumatoid arthritis patients with myelopathy treated without surgery are extremely poor. Surgical treatment is recommended for rheumatoid arthritis patients with myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
13

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 32 publications
1
38
0
13
Order By: Relevance
“…A recent study indicated that the natural course of RA patients with myelopathy managed by conservative treatments is poor [25]. In their study, all patients did not recover and were bedridden.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent study indicated that the natural course of RA patients with myelopathy managed by conservative treatments is poor [25]. In their study, all patients did not recover and were bedridden.…”
Section: Discussionmentioning
confidence: 92%
“…In their study, all patients did not recover and were bedridden. Furthermore, all patients had died within 3 years [25]. Casey [5] reported that no benefit was obtained except pain relief by surgical treatment of patients of Ranawat's class 3B.…”
Section: Discussionmentioning
confidence: 99%
“…However, the natural course of conservative therapy for RA patients accompanied with myelopathy is unfavorable and reported to result in persistent paralysis and bedridden state [20].…”
Section: Discussionmentioning
confidence: 99%
“…Decompression and fusion (including OFT) surgery in this type of rheumatoid patient has been shown to be beneficial in maintaining or improving the quality of life [1,2,7,8,10,11]. One of the technical advantages for the use of contemporary occipito-cervical rod-screw instrumentation is that an additional external brace such as a Halo-Vest is not necessary [3,[6][7][8]11].…”
Section: Discussionmentioning
confidence: 99%